2016
DOI: 10.1002/jssc.201600625
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of melamine in milk powder by using a magnetic molecularly imprinted polymer based on carbon nanotubes with ultra high performance liquid chromatography and tandem mass spectrometry

Abstract: A new magnetic molecularly imprinted polymer was coupled with ultra high performance liquid chromatography and tandem mass spectrometry for the selective determination of melamine in milk powder. The magnetic molecularly imprinted polymer has been prepared by using carbon nanotubes as the matrix, Fe O particles as the magnetic ingredient, melamine as the template molecule, methacrylic acid as the functional monomer, ethylene glycol dimethacrylate as the cross-linker and polyvinylpyrrolidone as the dispersant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Compared to traditional bulk‐imprinted strategy, surface imprinting has significant advantages, such as high template removal efficiency, fast mass transfer, controllable and regular shape, and good accessibility to target species . Moreover, MIP materials with superparamagnetic property are superior in easy handing and fast separation from sample matrix since they can be easily isolated by a magnet without retaining magnetism after the removal of the magnet . Fabrication of MIPs on superparamagnetic nanoparticles gives access to smart materials with dual functions of specific molecular recognition and magnetic separation.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to traditional bulk‐imprinted strategy, surface imprinting has significant advantages, such as high template removal efficiency, fast mass transfer, controllable and regular shape, and good accessibility to target species . Moreover, MIP materials with superparamagnetic property are superior in easy handing and fast separation from sample matrix since they can be easily isolated by a magnet without retaining magnetism after the removal of the magnet . Fabrication of MIPs on superparamagnetic nanoparticles gives access to smart materials with dual functions of specific molecular recognition and magnetic separation.…”
Section: Introductionmentioning
confidence: 99%
“…The peak at 1602 cm −1 is ascribed to the tensile vibration of C=C. The absorption band at 1731 cm −1 correspond to the tensile vibration of C=O from MAA. It indicated that EGDMA and MAA were involved in imprinting polymerization successfully.…”
Section: Resultsmentioning
confidence: 99%
“…From the FTIR spectra of MIPs (), an intensity peaks at 3445 cm −1 correspond to hydroxyl groups of phenols and aliphatic groups. At 2956 and 1457 cm −1 , there are C–H stretching vibration absorption peaks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thin imprinted monolayer coated on the surface of a solid support by a surface imprinting process holds a better mass transfer for target template, which is especially important for proteins that are easily enwrapped and difficult to remove completely from the polymer network. Up to now, many materials such as silica nanoparticles , silica nanotubes , alumina membrane , and magnetic nanoparticles have been adopted as the support materials of surface imprinting. Especially, silica nanoparticles are popular substrates for surface imprinting for many reasons including well‐established, numerous hydroxyl groups on the surface, chemical/mechanical stability, nontoxicity, and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%